Frequent Job Changes Can Signal Poor Work Attitude and Reduce Employability - Alain Cohn; Michel André Maréchal; Frédéric Schneider; Roberto A. Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study whether employment history provides information about a worker's "work attitude," i.e., the tendency to act cooperatively and reliably in the workplace. We conjecture that, holding all else equal, frequent job changes can indicate poor work attitude and that this information is transmitted through employment histories. We find support for this hypothesis across three studies that employ complementary lab, field, and survey experiments, as well as in labor market panel data. First, a tightly controlled laboratory labor market experiment demonstrates that prior employment information allows employers to screen for reliable and cooperative workers and that these workers obtain better employment outcomes. Second, we conduct a field experiment that varies the frequency of job changes in applicants' resumes and find that those with fewer job changes receive substantially more callbacks from prospective employers. Third, a survey experiment with Human Resources professionals confirms that the resume manipulations in the field study create different perceptions of work attitude and that these largely account for the callback differences. Finally, we find evidence consistent with our hypothesized relationships in empirical labor market data. Our work highlights the potential importance of job history as a signal of work attitude in labor markets, and points to a potential cost of frequent job changes.
Keywords: C90; C93; J01; E24; 330